Effect of grip width on electromyographical activity of upper body muscles at different loads - Kin-Isler, A.; Asci, A.; Aritan, S. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
The purpose of this study was to determine the effect of grip width on electormyographical activity of upper body muscles at different loads during non-bar release concentric bench press motion (CBP). Seventeen male handball players volunteered to participate in this study (Mage=18.23 ± 0.97 yrs; Mheight= 186.25 ± 8.99 cm; Mweight= 78.66 ± 14.95 kg; Mfat= 8.92 ± 7.71 %). Subjects performed ten explosive CBP at 50, 60, 70, 80 and 100 % of 1-RM at 100 and 200 % of their biacromial distance (BAD) in random order. The EMG activity of clavicular pectoralis major (CPM), sternocostal pectoralis major (SPM), anterior deltoid (AD) and triceps muscles of dominant side were recorded by using surface electrodes. Maximum force was calculated for each lift at different grip widths and loads by inverse dynamics and for each muscle root mean squares of EMG signals were calculated from the start of the lift till the formation of maximum force. The results of 2*5 (grip width*load) MANOVA with repeated measures indicated significant main effect for grip width (Hoteling`s T2=1.105; F(4,13)=3.591; p<.05) and follow-up univariate analysis revealed that triceps muscle had lower activity level during 200 % BAD than 100 % BAD (F(4,13)=13.216; p<.01). In addition, significant main effect for load was also found (Hoteling`s T2=0.933; F(16,238)=3.469; p<.01) and univariate analysis indicated that during CBP triceps muscles` activation at 60 % of 1- RM was higher than the rest of loads (F(16,238)=10.234; p<.01). Furthermore, grip width*load interaction was significant (Hoteling`s T2=0.781; F(16,238)=2.904; p<.01) and univariate analysis indicated that SPM (F(16,238)=2.651; p<.05) and triceps (F(16,238)=4.829; p<.01) muscles` activation levels changed significantly according to grip width and CBP loads. In conclusion, it can be stated that grip width and different loads resulted in differences in the myoelectrical activity of upper body muscles during concentric only non-bar release bench press motion.